Shadow footprints and the provision of digital behavioral data - Estelle Clements; Marcus Horwood (Journal of Digital Social Research, 2024)
We introduce the concept of shadow footprints as a means of understanding privacy challenges in the information environment. Growing emphasis on the impact of citizens sharing their personal data goes far beyond the individual, with the increased capacity of algorithms to formulate shadow footprints that inform as much about persons absent from data, as persons present. Data extrapolated from small groups have demonstrated robust utility when applied to larger populations. Individuals who have opted to keep their data private, or who have been unaware that data about their private lives has been extracted from the involvement of their fellow citizens from digital behavioral data, suggest the possibility that informed consent has been circumvented, or not fully investigated. This is increasingly concerning when one considers the potential to impact the body politic through behavioral manipulation drawn from such data. These issues must be considered in the context of ethical and litigious standards to inform robust policy frameworks, legal regulation, and the provision of incentives necessary to provide guidance and civic protections, as well as adherence to good ethical practice.